2018
DOI: 10.1186/s12866-018-1309-2
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning and characterization of vanillin dehydrogenase from Streptomyces sp. NL15-2K

Abstract: BackgroundStreptomyces sp. NL15-2K, previously isolated from the forest soil, features an extensive catabolic network for lignin-derived aromatic compounds, including pathways transforming ferulic acid to vanillin, vanillic acid, and protocatechuic acid. To successfully use Streptomyces sp. NL15-2K as a biocatalyst for vanillin production, it is necessary to characterize the vanillin dehydrogenase (VDH) that degrades the produced vanillin to vanillic acid, as well as the gene encoding this enzyme. Here, we clo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…These aromatic compounds derived from G- and S-lignins are degraded through vanillate (VA) and syringate (SA), respectively 12,16 . In addition to SYK-6 catabolism, it has been reported that lignin-derived aromatic compounds, including ferulate, sinapate, vanillin, and syringaldehyde, are degraded via VA and SA in many microorganisms 9,1720 . Therefore, VA and SA are considered to be the key intermediate metabolites in the microbial degradation of lignin.…”
Section: Introductionmentioning
confidence: 99%
“…These aromatic compounds derived from G- and S-lignins are degraded through vanillate (VA) and syringate (SA), respectively 12,16 . In addition to SYK-6 catabolism, it has been reported that lignin-derived aromatic compounds, including ferulate, sinapate, vanillin, and syringaldehyde, are degraded via VA and SA in many microorganisms 9,1720 . Therefore, VA and SA are considered to be the key intermediate metabolites in the microbial degradation of lignin.…”
Section: Introductionmentioning
confidence: 99%
“…The lower conversion rate on strain S38 reveals the correlation of the strain isolate source of undisturbed peatlands with lower lignin monomers such as vanillin compared with the strain S46 isolate source on disturbed peatlands. Different theories exist in the literature regarding vanillin regarding some of the degradation products after conversion from vanillic acid to protocatechuic acid (Nishimura et al, 2018), while another found is guaiacol (Fig. S6), as reported by previous research (Álvarez-Rodríguez et al, 2003;Ito et al, 2016;Witthuhn et al, 2012).…”
Section: Discussionmentioning
confidence: 72%
“…These enzymes transform the secondary metabolite vanillin to vanillic acid, which is further converted to protocatechuate. Vanillin dehydrogenases from various bacteria were reported to exhibit broad substrate specificity toward various aromatic aldehydes, such as isovanillin, veratraldehyde, anisaldehyde, protocatechualdehyde, p -hydroxybenzaldehyde, salicylaldehyde, and benzaldehyde ( Masai et al 2007 ; Mitsui et al 2010 ; Graf et al 2016 ; Nishimura et al 2018 ). The genes fadD and fadB encode for a putative feruloyl-CoA synthase and vanillin synthase, respectively, enabling the catabolism of ferulic acid through its conversion to vanillin, which is further transformed by vanillin dehydrogenase and vanillate O -demethylase ( Overhage et al 1999 ).…”
Section: Resultsmentioning
confidence: 99%